(The Components and Factors That Helped in Establishing the Kingdom of Saudi Arabia (850-1351 AH/1446-1932 AD - Al - Zaher, Ahmed Maseeb; Al - Aqrabawi, Moayad Tawfiq Aql Haidar (Arab Journal for Sciences and Research Publishing, 2018)
The study aimed at highlighting the establishment of Kingdom of Saudi Arabia, in terms of the components and factors that helped in establishing the Kingdom during the period 850-1351 AH, i.e. 1446-1932 AD. The study addressed arrangement of the components to crystallize the factors of establishing the Kingdom; then the appearance of the primary factors to establish the Saudi State, which were characterized by being internal factor helped in this direction. The study further tackled the traits of the successful leader, who managed to control the affairs of the state, through patience and fortitude, which were in Abdul Aziz Bin Abdul Rahman Al Saud, who also possessed many attributes. Finally, the researchers explored the external factors that helped in establishing the Third Saudi State.  The study adopted the analytic descriptive method, i.e. describing the events, analyzing them, and then coming out with findings in the light of the results of these analyses. The results underlined the effectiveness of the religious factor, which played a positive role in establishing the Kingdom of Saudi Arabia. The resume of Abdul Aziz Bin Abdul Rahman Al Saud was characterized by human wisdom, while expanding his rule. On the other hand, patience and will were coincident traits in Al Saud in general, and Abdul Aziz in particular. Abdul Aziz Bin Abdul Rahman gained good lessons of the mistakes his ancestors fell in, whether in the administrative aspect or that of managing the battles.
Keywords: The Kingdom of Saudi Arabia; Al Saud; Abdul Aziz bin Abdul Rahman Al Saud; the foundations; the factors